Effect of Natural Rubber Electrolytes Modified with CuCl2, NiCl2 and Active Carbon - Borowski, Tomasz (Asian Journal of Chemistry, 2010)
Natural rubber, as a solvent and repository of electric charges, starts to gain these properties after adding to natural rubber CuCl2 or NiCl2 in the form of methanol solution with addition of active carbon. Electrical conductivity of such a natural rubber-active carbon system with added natural rubber CuCl2 or NiCl2 equals to 3.5 × 10-6 to 3.8 × 10-6 S cm-1 at a room temperature of 293 K and a frequency of 10 kHz. The examined electrolytes were tested for the frequency range of 1 to 25 kHz. These polymer electrolyte systems may find their application as materials for anticorrosive and antielectrostatic protection of fuel or hazardous material tanks.